Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

solve for x -3(x-1)+8(x-3)=6x+7-5x

Sagot :

luana
[tex]x-3(x-1)+8(x-3)=6x+7-5x\\\\ x-3x+3+8x-24=6x+7-5x\ \ \ \ | grouping\ similar\ factors\\\\ 6x-21=-x+7\ \ \ | add\ x\\\\ 7x-21=7\ \ \ |add\ 21\\\\ 7x=28\ \ \ |divide\ by\ 7\\\\ x=4\\\\ Solution\ is\ x=4.[/tex]